2000
DOI: 10.1007/pl00008344
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of meconium on pulmonary surfactant function tested in vitro using the stable microbubble test

Abstract: The stable microbubble test is an effective indirect method that tests the changes in surfactant quantity. In the in vitro experiment, we observed an inhibitory effect of meconium on the surfactant activity using the stable microbubble test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Various clinical situations such as pulmonary haemorrhage, meconium aspiration syndrome (MAS), pulmonary infection and atelectasis have been shown to liberate inflammatory mediators that damage type II pneumocytes and inactivate surfactant [20,21]. Surfactant replacement therapy could thus be useful as a supporting treatment in this population of newborns with secondary or transient surfactant deficiency.…”
Section: Which Infants Should We Treat With Exogenous Surfactant Thermentioning
confidence: 99%
“…Various clinical situations such as pulmonary haemorrhage, meconium aspiration syndrome (MAS), pulmonary infection and atelectasis have been shown to liberate inflammatory mediators that damage type II pneumocytes and inactivate surfactant [20,21]. Surfactant replacement therapy could thus be useful as a supporting treatment in this population of newborns with secondary or transient surfactant deficiency.…”
Section: Which Infants Should We Treat With Exogenous Surfactant Thermentioning
confidence: 99%
“…The accelerated surfactant subtype conversion in the presence of meconium means the increased consumption of surface-active large and heavy surfactant aggregates. Recent studies [4,18,20,26] have reported the interaction between pulmonary surfactant and human meconium as indicated by delayed adsorption and increased minimum surface tension (i.e. inhibition of biophysical properties of pulmonary surfactant).…”
Section: Discussionmentioning
confidence: 99%
“…Although the interactions between pulmonary surfactant and meconium have been previously reported [4,5,12,18,20,26], no prior study has paid attention to the eect of meconium on the rate of surfactant subtype conversion (i.e. extracellular surfactant metabolism).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Meconium inhibits surfactant function directly, and thereby increases the minimum and maximum surface tension in the alveolus, and lowers the spreading rate of surfactant. [1][2][3][4][5] Information on surfactant concentration and composition in MAS is scarce. Bronchoalveolar lavage (BAL) fluid from eight infants with MAS receiving mechanical ventilation had no differences in phospholipid and surfactant protein-A (SP-A) content compared with control subjects.…”
mentioning
confidence: 99%